The wonderful wizard of Oz - Baum, L. Frank (Lyman Frank), 1856-1919 (First Avenue Editions, a division of Lerner Publishing Group, 2014)
After a cyclone transports her to the land of Oz, Dorothy must seek out the great Wizard in order to return to Kansas.